A Highly Rare Cause of Lumbar Spondylodiscitis with Epidural Abscess: Actinomyces israelii. (12th June 2014) - Kapmaz, Mahir; Gülşen, İsmail; Kış, Naciye; Başaran, Seniha; Öksüz, Lütfiye; Gürler, Nezahat
Abstract : Actinomyces species may lead to slowly progressive infection of almost any site once mucosal breakdown exists; hence, it has the name "great pretender." Its diagnosis may be unthinkable unless proper cultures/histologies are taken. We describe a patient with lumbar spondylodiscitis and epidural abscess. This is an exceptional another disease by actinomycosis.